The Relationship Between Knowledge and the Implementation of Infusation Installation According to Standard Operational Procedures (Spo) for Nurses in the Mayapada Inpatition Room of Hospital Tangerang - Wulandari, Dewa Ayu Putu Sri; Mubarok, M. Fuad Al; Ria, Roma Tao Toba Muara; Lelasari, Margarita Dewi; Warsini, Anastasia; Situmeang, Marsondang (Journal of World Future Medicine, Health and Nursing, 2024)
Insertion of an IV is a common and basic invasive procedure carried out by nursing staff on patients being treated in hospital. The aim of this research is to determine whether there is a relationship between nurses’ knowledge about infusion installation and the implementation of infusion installation according to Standard Operating Procedures (SPO). This research method uses a quantitative correlation method with a cross sectional approach. The sampling technique used the Slovin formula with an assumption of an error rate of 10%, resulting in 56 samples. Analysis of the data in this study using the Chi Square test resulted in a value of p = 0.512, which means 0.512 > 0.05 and the Fisher’s Exact test and obtained a result of p = 0.580, which means 0.580 > 0.05, so the conclusion is that there is no significant relationship between knowledge and implementation of infusion installation according to Standard Operating Procedures (SPO). Suggestions from this research are that it is hoped that nurses can increase knowledge about infusion procedures and consistency in carrying out infusion procedures according to Standard Operating Procedures (SPO).